Innovative Sol-gel functionalized polyurethane foam for sustainable water purification and analytical advances - Alwael, H.; Alsulami, A. N.; Abduljabbar, T. N.; Oubaha, M.; El-Shahawi, M. S. (Frontiers in Chemistry, 2024)
Nanomaterial combined polymeric membranes such as polyurethane foams (PUFs) have garnered enormous attention in the field of water purification due to their ease of management and surface modification, cost-effectiveness, and mechanical, chemical, and thermal properties. Thus, this study reports the use of novel Sol-gel impregnated polyurethane foams (Sol-gel/PUFs) as new dispersive solid phase microextractors (d- µ SPME) for the efficient separation and subsequent spectrophotometric detection of Eosin Y (EY) textile dye in an aqueous solution with a pH of 3–3.8. The Sol gel, PUFs, and Sol gel–impregnated PUFs were characterized using scanning electron microscopy (SEM), goniometry measurements, dynamic light scattering (DLS), energy dispersive spectroscopy (EDS), UV-Visible, and FTIR spectra. Batch experiment results displayed a remarkable removal percentage (96% ± 5.4%) of the EY from the aqueous solution, with the total sorption time not exceeding 60 min. These data indicate rate-limited sorption via diffusion and/or surface complex ion associate formations after the rapid initial sorption steps. A pseudo-second order kinetic model thoroughly explained the sorption kinetics, providing a sorption capacity (qe) of 37.64 mg g−1, a half-life time (t1/2) of 0.8 ± 0.01 min, and intrinsic penetration control dye retention. The thermodynamic results revealed a negative value for ΔG⁰ (−78.07 kJ mol−1 at 293 K), clearly signifying that the dye uptake was spontaneous, as well as a negative value for ΔH⁰ (−69.58 kJ mol−1) and a positive value for ΔS⁰ (147.65 J mol−1 K−1), making clear the exothermic nature of EY adsorption onto the sorbent, with a growth in randomness at the molecular level. A ternary retention mechanism is proposed, involving the “weak base anion exchanger” of (–CH2–OH+ –CH2–) (Dye anion)−Sol-gel/PUF and/or (–NH2+ –COO-) (Dye anion)−Sol-gel/PUF via solvent extraction and “surface adsorption” of the dye anion on/in the Sol-gel/PUFs membranes in addition to H-bonding, including surface complexation and electrostatic π-π interaction, between the dye and the silicon/zirconium oxide (Si-O-Zr) and siloxane (Si-O-Si) groups on the sorbent. Complete extraction and recovery (93.65 ± 0.2, −102.28 ± 2.01) of EY dye with NaOH (0.5 M) as a proper eluting agent was achieved using a sorbent-packed mini column. In addition, the established extractor displayed excellent reusability and does not require organic solvents for EY enrichment in water samples, making it a talented nominee as a novel sorbent for EY sorption from wastewater. This study is of great consequence for expanding the applicatio1n of Sol-gel/PUFs in developing innovative spectrophotometric sensing strategies for dye determination. In view of this, it would also be remarkable to perform future studies to explore the analytical implications of this extractor regarding safety and environmental and public health issues associated to the pollutant.